Eye-care utilization among a Canadian diabetic refugee population: retrospective cohort study of an interdisciplinary care model. (September 2021) - Tanya, Stuti M; He, Bonnie; Aubrey-Bassler, Christine
Introduction: Vision health is an important and underutilized health service among newly arrived refugees in Canada, yet the body of literature on eye-care delivery in this population is limited. The study objective was to identify patterns of eye-care utilization among refugee patients with type 2 diabetes mellitus (T2DM) in Newfoundland and Labrador (NL) under an interdisciplinary clinic model comprised of family physicians, eye-care providers, and settlement services. Methods: This was a retrospective cohort study at the Memorial University Family Medicine clinic. All patients with a new T2DM diagnosis between 2015–2020 were included. Data were described using basic statistics and unpaired t-tests. This study received full ethics approval. Results: Seventy-three (18 refugee, 55 non-refugee) patients were included. Refugees had a higher rate of referral to an eye-care provider ( p = 0.0475) and were more likely to attend their eye-care provider appointment than non-refugees ( p = 0.016). The time from diagnosis to referral was longer for refugees than non-refugees ( p = 0.0498). A trend towards longer time from referral to appointment attendance for refugees than non-refugees was noted ( p = 0.9069). Discussion: Refugee patients had higher rates of referral to eye-care providers and utilization of eye-care services. However, refugees also experienced a longer time to access vision screening services suggesting possible gaps in accessible care delivery. This suggests that the interdisciplinary model of care may be effective in referring refugee patients for vision screening and there may be a role for increased collaboration across family physicians, eye-care providers, and settlement services to improve accessibility of vision screening services.